Human Mobility Patterns at the Smallest Scales (Communications in Computational Physics, 2018)
We present a study on human mobility at small spatial scales. Differentlyfrom large scale mobility, recently studied through dollar-bill tracking and mobilephone data sets within one big country or continent, we report Brownian features ofhuman mobility at smaller scales. In particular, the scaling exponents found at thesmallest scales are typically close to one-half, differently from the larger values for theexponent characterizing mobility at larger scales. We carefully analyze 12-month dataof the Eduroam database within the Portuguese university of Minho. A full procedureis introduced with the aim of properly characterizing the human mobility within thenetwork of access points composing the wireless system of the university. In particular,measures of flux are introduced for estimating a distance between access points. Thisdistance is typically non-Euclidean, since the spatial constraints at such small scalesdistort the continuum space on which human mobility occurs. Since two different exponentsare found depending on the scale human motion takes place, we raise thequestion at which scale the transition from Brownian to non-Brownian motion takesplace. In this context, we discuss how the numerical approach can be extended tolarger scales, using the full Eduroam in Europe and in Asia, for uncovering the transitionbetween both dynamical regimes.